Analysis of dose verification results for 924 intensity‐modulated radiation therapy plans. Issue Volume 2:Issues 4(2018) (19th December 2018) - Wu, Shizhang; Chen, Jinhu; Li, Zhenjiang; Qiu, Qingtao; Wang, Xingli; Li, Chengqiang; Yin, Yong
Abstract: Objective: Intensity‐modulated radiation therapy (IMRT) plays an increasingly important role in clinical applications, and dose verification is particularly crucial for each patient. In the present study, we retrospectively analyzed the results of dose verification in 924 actual IMRT plans, including the relationship between gamma pass rates and the location of lesions, and the total number of monitor units, and the maximum area of the collected dose. Methods: All the 924 IMRT plans implemented in a Varian Trilogy accelerator between 1 January 2014 and 31 March 2016 at Shandong Cancer Hospital were acquired. The Varian Eclipse planning system was used for all treatment planning and verification. Then, actual implemented plans were transplanted into a water phantom. Subsequently, the derived fluence was compared with the actual measured fluence by gamma analysis with the gamma criteria (3%/3 mm). Results: A total of 924 IMRT plans were categorized into six groups, including the brain, head and neck, chest, abdomen, pelvis, and breast. The gamma pass rate average was >98% for 902 IMRT plans, whereas 22 plans did not pass the first time. A correlation was observed between the treatment site and gamma pass rate ( P  = 0.017). Meanwhile, a negative correlation was observed between the gamma pass rate and the total number of monitor units ( P  < 0.001), and the largest area of the acquisition dose (P < 0.001), respectively. Varian Trilogy accelerator IMRT QA data has a stable pass rate with a 100 confidence limit (CL) value of 95.19. Conclusion: There was a correlation between the pass rate and the treatment site, the total number of monitor units, and the maximum area of collected dose. When using Mapcheck for patient plan dose verification, the gamma pass rate is very high, and only a few of them need to be analyzed.